Chương I - Căn bậc hai. Căn bậc ba

QE

Rút gọn các biểu thức sau:

\(C=\left(\dfrac{\sqrt{a}}{\sqrt{a}-1}-\dfrac{\sqrt{a}}{a-\sqrt{1}}\right):\dfrac{\sqrt{a}+1}{a-1}\)

TL
17 tháng 7 2021 lúc 22:38

ĐK: `a \ne 1 ; a>=0` 

`C=(\sqrta/(\sqrta-1)-\sqrta/(a-1)) : (\sqrta+1)/(a-1)`

`=(\sqrta/(\sqrta-1) - \sqrta/((\sqrta-1)(\sqrta+1))) . (a-1)/(\sqrta+1)`

`= (\sqrta(\sqrta+1)-\sqrta)/((\sqrta-1)(\sqrta+1)) . ((\sqrta-1)(\sqrta+1))/(\sqrta+1)`

`= a/(\sqrta+1)`

Bình luận (0)
NT
17 tháng 7 2021 lúc 22:41

Ta có: \(C=\left(\dfrac{\sqrt{a}}{\sqrt{a}-1}-\dfrac{\sqrt{a}}{a-1}\right):\dfrac{\sqrt{a}+1}{a-1}\)

\(=\dfrac{a+\sqrt{a}-\sqrt{a}}{\left(\sqrt{a}-1\right)\left(\sqrt{a}+1\right)}:\dfrac{1}{\sqrt{a}-1}\)

\(=\dfrac{a}{\sqrt{a}+1}\)

Bình luận (1)

Các câu hỏi tương tự
QE
Xem chi tiết
QE
Xem chi tiết
QE
Xem chi tiết
AQ
Xem chi tiết
QE
Xem chi tiết
QE
Xem chi tiết
LL
Xem chi tiết
LG
Xem chi tiết
LG
Xem chi tiết